[Conference report] Arctic Discourses 2008 - Lindgren Leavenworth, Maria; Svensson, Maria Helena (Journal of Northern Studies, 2008)
The project “Arctic Discourses,” based in the Faculty of Humanities, University of Tromsø focuses on investigations of fictional texts, historical and scientific documents and travelogues from the mid nineteenth century to the present day. Arctic Discourses was also the name of the conference held February 21–23 at the University of Tromsø, arranged by the project coordinators Anka Ryall, Johan Schimanski and Henning Howlid Waerp, and the project’s foci were clearly visible despite very varied papers.